Oxygen uptake response to an 800-m running race - Thomas, C.; Hanon, C.; Perrey, S.; Le Chevalier, J. -M.; Couturier, A.; Vandewalle, H. (International Journal of Sports Medicine, 2005)
We tested the hypothesis that time course of O2 uptake (VO2) measured during a supramaximal exercise performed in the field is driven to maximal oxygen uptake (VO2max). On an outdoor track, five middle-distance male runners first performed a test to determine VO2max and a supramaximal 800-m running test at least two days apart. VO2 response was measured from the start to the end of exercise with the use of a miniaturised telemetric gas exchange system (Cosmed K4). VO2max was reached by all subjects 45 ± 11 s (mean ± SD) after the onset of the 800-m race (i.e., 316 ± 75 m), and was maintained during the next 33 ± 6 s (i.e., 219 ± 41 m). The mean relative exercise intensity of the 800 m was 120 % VO2max. An unexpected significant decrease in VO2 (24.1 ± 7.0 %; p < 0.05) was observed in all subjects during the final 38 ± 17 s (i.e., the last 265 ± 104 m). We concluded that, at onset of a simulated 800 m running event, VO2 is quickly projected towards the VO2max, and then becomes limited by the achievable VO2max. This race profile shown by all athletes is in some contrast to what can be expected from earlier findings in a laboratory setting.